D-dimer as a potential biomarker in chronic obstructive pulmonary disease - Patel, Anish V.; Tyagi, Mayurika S.; Mittal, Adreena; Chandra, Sumit; Kausar, Hina; Dhandayuthapani, Sivanesan (European Journal of Clinical and Experimental Medicine, 2025)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Despite signs of drop in tuberculosis in the middle of the twentieth century, up to 75% of men were smokers at that time, which contributed to the epidemic of chronic obstructive pulmonary disease (COPD) in the latter half of the century. The present study was conducted with the main focus of establishing a relation between D-dimer and lung function in patients with COPD. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;"> Material and methods. A hospital-based observational cross-sectional study involved 108 subjects, divided into 54 cases (COPD patients) and 54 healthy controls (41-80 years old). The dry volume spirometer was used to assess the lung health of the study population. D-dimer assay was performed on peripheral blood drawn from study subjects using the second generation latex-enhanced immunoturbidimetric assay on the Diagon Fully Automatic COAG XL Coagulation Analyzer. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;"> Results. Spirometry tests revealed COPD patients showing reduced lung function (42.59% with normal, 51.85% with mild, and 5.56% with moderate degree of forced expiratory volume in 1 second and forced expiratory volume in 1 second/ forced vital capacity). Patients with COPD under different age groups and both the genders showed an elevated level (p<0.05) of D-dimer in correlation with the spirometry measurements. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;"> Conclusion. The D-dimer is promising plasma biomarker which demonstrated a strong correlation with the spirometry measurements and different morphological categories in patients with COPD. The D-dimer could serve as a reliable biomarker for validating and confirming the various morphological classifications among individuals with COPD.